Participatory Management Model of Private Schools under the Office of the Private Education Commission - Sutabutra, Tanai; Jinadattiyo, Phramaha Kraiwan (Journal of Dhamma for Life, 2026)
The objectives of this research were: 1) to study the components of participatory management in private schools under the Office of the Private Education Commission, 2) to develop a participatory management model for these schools, and 3) to evaluate and validate the model. This study employed a mixed methods research approach. The sample consisted of 335 private elementary schools under the Office of the Private Education Commission. The respondents included school directors, deputy directors, teachers, and school board members—four individuals from each school—totaling 1,340 participants. Data collection tools included interviews, questionnaires, and evaluation forms. Data were analyzed using descriptive statistics such as frequency, percentage, standard deviation, and exploratory factor analysis. The research findings were as follows: 1. The study identified a total of 148 variables constituting six core components of participatory management in private schools under the Office of the Private Education Commission. 2. The developed participatory management model comprised 6 key components with 114 variables: 1) Organizational Leadership Skills (23 variables) 2) Participation in Operations (20 variables) 3) Organizational Commitment (19 variables) 4) Internal Communication (22 variables) 5) Participation in Decision-Making (17 variables) 6) Creative Change Management (13 variables) 3.The developed model was evaluated and validated as accurate, appropriate, feasible, and beneficial, with an overall mean score ( ) of 4.89, indicating strong agreement with theoretical frameworks and research principles.